Fatty Acid Compositions of Six Wild Edible Mushroom Species - Pelin Günç Ergönül; Ilgaz Akata; Fatih Kalyoncu; Bülent Ergönül (The Scientific World Journal)
The fatty acids of six wild edible mushroom species (Boletus reticulatus, Flammulina velutipes var. velutipes, Lactarius salmonicolor, Pleurotus ostreatus, Polyporus squamosus, and Russula anthracina) collected from different regions from Anatolia were determined. The fatty acids were identified and quantified by gas chromatography and studied using fruit bodies. Fatty acid composition varied among species. The dominant fatty acid in fruit bodies of all mushrooms was cis-linoleic acid (18 : 2). Percentage of cis-linoleic acid in species varied from 22.39% to 65.29%. The other major fatty acids were, respectively, cis-oleic, palmitic, and stearic acids. Fatty acids analysis of the mushrooms showed that the unsaturated fatty acids were at higher concentrations than saturated fatty acids.